Urban regeneration. A manifesto for transforming UK cities in the age of climate change. - Lehmann, Steffen (Palgrave Macmillan, 2019)
This book explores and offers guidance on the complex process of how to transform cities, continuing the unfinished project of the seminal 1999 text "Towards an urban renaissance. Mission statement". It is a 21st-century manifesto of urban principles compiled by a prominent urbanist, for the regeneration of UK cities, focusing on the characteristics of a "good place" and the strategies of sustainable urbanism. It asks readers to consider how we can best transform the derelict, abandoned and run-down parts of cities back into places where people want to live, work and play. The book frames an architecture of re-use that translates and combines the complex "science of cities" and the art of urban and architectural design into actionable and practical guidance on how to regenerate cities. Fascinated by the typology and value of the compact UK and European city model, the author introduces the concept of "high density without high buildings" as a solution that will make our cities compact, walkable, mixed-use and vibrant again.
Keywords: Stadterneuerung; Stadtentwicklungsplanung; Klimawandel; Klimaanpassung; Transformation; Nachhaltige Entwicklung; Leitbild; Kompakte Stadt; Bebauungsdichte; Bebauungsstruktur; Stadtgestaltung; Resilienz; Ressourcenschonung